Neuronal networks underlying the conjoint modulation of response selection by subliminal and consciously induced cognitive conflicts - Bensmann, Wiebke; Zink, Nicolas; Mückschel, Moritz; Beste, Christian; Stock, Ann-Kathrin (Brain structure & function, 2019)
Goal-directed behavior has been shown to be affected by consciously and subliminally induced conflicts. Both types of conflict conjointly modulate behavioral performance, but the underlying neuronal mechanisms have remained unclear. While cognitive control is linked to oscillations in the theta frequency band, there are several mechanisms via which theta oscillations may enable cognitive control: via the coordination and synchronization of a large and complex neuronal network and/or via local processes within the medial frontal cortex. We, therefore, investigated this issue with a focus on theta oscillations and the underlying neuronal networks. For this purpose, n = 40 healthy young participants performed a conflict paradigm that combines conscious and subliminal distractors while an EEG was recorded. The data show that separate processes modulate the theta-based activation and organization of cognitive control networks: EEG beamforming analyses showed that variations in theta band power generated in the supplementary motor area reflected the need for control and task-relevant goal shielding, as both conflicts as well as their conjoint effect on behavior increased theta power. Yet, large networks were not modulated by this and graph theoretical analyses of the efficiency (i.e. small worldness) of theta-driven networks did not reflect the need for control. Instead, theta network efficiency was decreased by subliminal conflicts only. This dissociation suggests that while both kinds of conflict require control and goal shielding, which are induced by an increase in theta band power and modulate processes in the medial frontal cortex, only non-conscious conflicts diminish the efficiency of theta-driven large-scale networks.
Keywords: Adolescent; reakční čas; Nerve Net; chování; Male; Female; Theta Rhythm; mladý dospělý; Priming; vědomí; nervová síť; Reaction Time; Young Adult; Electroencephalography; EEG; mužské pohlaví; kognice; elektroencefalografie; ženské pohlaví; Adult; Psychomotor Performance; Executive Function; Behavior; mladiství; Frontal Lobe; Flanker; dospělí; Cognition; Consciousness; exekutivní funkce; psychomotorický výkon; Theta oscillations; lidé; Humans; Small world networks; čelní lalok; theta rytmus EEG; Response conflict